2022
DOI: 10.32866/001c.33830
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Modal Shift towards Motorized Two-wheelers in Dhaka, Bangladesh

Abstract: Based on in-depth interviews of 17 key informants in Dhaka, Bangladesh, this paper explores the reasons behind the observed modal shift toward motorized two-wheelers that occurred with the COVID-19 pandemic, along with its implications. Analysis of the key informants' perspectives revealed that individuals' inclination towards motorized two-wheelers occurs because of maintaining physical distance, lack of walking and bicycling infrastructure, the high social status associated with motorized two-wheelers, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Bangladesh Institute of Development Studies (BIDS) conducted a survey in May 2020 that found that almost 16.4 million people in Bangladesh are sliding below the poverty line due to the Covid-19 pandemic (Jamal, 2020). Since this pandemic's devastating effects have been unfolding rapidly, it becomes imperative for the government and private actors to understand and address the extent of workers' hardship on their livelihoods.…”
Section: Discussionmentioning
confidence: 99%
“…Bangladesh Institute of Development Studies (BIDS) conducted a survey in May 2020 that found that almost 16.4 million people in Bangladesh are sliding below the poverty line due to the Covid-19 pandemic (Jamal, 2020). Since this pandemic's devastating effects have been unfolding rapidly, it becomes imperative for the government and private actors to understand and address the extent of workers' hardship on their livelihoods.…”
Section: Discussionmentioning
confidence: 99%